The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1517/14728222.2010.524208
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tryptophan hydroxylase 2 in affective disorder

Abstract: More comprehensive study of TPH2 genetics is needed to increase the clinical value of the enzyme as a predictor of affective disorder risk and efficacy of antidepressant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 131 publications
1
16
0
Order By: Relevance
“…Although not shown in the present study, insufficient tph2 or lack of serotonin has been shown to lead to mood disorders such as depression [30], schizophrenia [31] and neurodegeneration such as Alzheimer’s dementia [32], [33]. Our mRNA expression study clearly demonstrated that unloading-induced tph2 deficiency is prevented by pre-application of knee loading.…”
Section: Discussionsupporting
confidence: 39%
“…Although not shown in the present study, insufficient tph2 or lack of serotonin has been shown to lead to mood disorders such as depression [30], schizophrenia [31] and neurodegeneration such as Alzheimer’s dementia [32], [33]. Our mRNA expression study clearly demonstrated that unloading-induced tph2 deficiency is prevented by pre-application of knee loading.…”
Section: Discussionsupporting
confidence: 39%
“…This member of the aminoacid hydroxylase family catalyzes the formation of the direct 5-HT precursor, 5-hydroxy-tryptophan (5-HTP) from tryptophan (Walther et al, 2003). Multiple noncoding or loss-of-function polymorphisms in the TPH2 gene have been identified as potential genetic risk factors for several psychiatric illnesses, including bipolar disorder, major depression, attention deficit hyperactivity disorder (ADHD), and schizophrenia (Popova and Kulikov, 2010;Russo et al, 2009;Waider et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding these two proteins have been repeatedly, although controversially, linked to various psychiatric disorders in humans (Canli et al, 2008; Gao et al, 2012; Hariri et al, 2005; Hariri & Holmes, 2006; Popova & Kulikov, 2010; Waider et al, 2011; Zhou et al, 2005) and influence anxiety-related personality traits among healthy individuals (Gutknecht et al, 2007; Lesch et al, 1996; Reuter, Kuepper, & Hennig, 2007; Sen, Burmeister, & Ghosh, 2004). …”
mentioning
confidence: 99%
“…The TPH2 enzyme is another important regulator of serotonergic function and there exist several polymorphisms in the human TPH2 gene (Gao et al, 2012; Popova & Kulikov, 2010). Unlike 5-HTTLPR, there is no single TPH2 polymorphism that has been particularly well studied or characterized, although several are linked to psychiatric disease, altered amygdala activity and anxiety-related personality traits in a manner similar to 5-HTTLPR (Popova & Kulikov, 2010).…”
mentioning
confidence: 99%